2006
DOI: 10.1007/s00401-005-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of neurodegeneration in neuronal ceroid-lipofuscinoses

Abstract: Neuronal ceroid-lipofuscinoses (NCL) are a group of neurodegenerative diseases and autosomal recessive lysosomal storage disorders. We examined the involvement of cell death, oxidative stress, and glutamate excitotoxicity using immunohistochemistry against Bcl-2, Bcl-x, oxidative products to proteins, lipids and DNA, calcium-binding proteins (calbindin-D28K, parvalbumin, calretinin), and glial glutamate transporters (excitatory amino acid transporters 1 and 2), in addition to terminal deoxynucleotidyl transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…It is possible that the aforementioned changes in this analysis may be secondary to epileptic seizures rather than causative. However, we immunohistochemically clarified the accumulation of oxidative products in the brains of neuronal ceroidlipofuscinosis (NCL), which can also cause PME [30,31]. Cases of late infantile and protracted juvenile types of NCL demonstrated accumulation of 8-OHdG and 4-HNE in the cerebral cortex.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that the aforementioned changes in this analysis may be secondary to epileptic seizures rather than causative. However, we immunohistochemically clarified the accumulation of oxidative products in the brains of neuronal ceroidlipofuscinosis (NCL), which can also cause PME [30,31]. Cases of late infantile and protracted juvenile types of NCL demonstrated accumulation of 8-OHdG and 4-HNE in the cerebral cortex.…”
Section: Discussionmentioning
confidence: 98%
“…A study found that calcium-binding proteins linked to GABAergic interneurons in the cortex and cerebellum were disrupted in patients with LINCL. 24 An additional postmortem study of 13 case subjects with LINCL found a moderate-to-severe loss of myelin and mild-to-moderate gliosis in the periventricular white matter of 10 of 13 case subjects. 2 Increased signal intensity in the periventricular white matter on T2-weighted MR images in patients with LINCL was correlated with histology confirming atrophy.…”
Section: 17mentioning
confidence: 97%
“…In MPSIIIB, enhanced oxidative stress resulted in protein, lipid, and DNA oxidation (24), and an oxidative imbalance was found in MPSI (25). In NCLs, elevated ROS and superoxide dismutase levels were suggested to be downstream to ER stress (26), a significant increase in manganese-dependent superoxide dismutase activity was detected in fibroblasts and brain extracts from CLN6 sheep (27), and increased expression of 4-hydroxynonenal was detected in late infant and juvenile forms of NCL (28).…”
Section: Oxidative Stress and Free Radicalsmentioning
confidence: 99%